2002
DOI: 10.1901/jaba.2002.35-105
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cumulative Practice on Mathematics Problem Solving

Abstract: This study compared three different methods of teaching five basic algebra rules to college students. All methods used the same procedures to teach the rules and included four 50-question review sessions interspersed among the training of the individual rules. The differences among methods involved the kinds of practice provided during the four review sessions. Participants who received cumulative practice answered 50 questions covering a mix of the rules learned prior to each review session. Participants who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
1
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 37 publications
4
74
1
6
Order By: Relevance
“…Other studies have reported benefits of interleaving on the learning of geometric concepts (e.g., Taylor & Rohrer, 2010) and algebraic rules (e.g., Mayfield & Chase, 2002). A small but growing number of studies has also reported benefits of interleaving for other types of cognitive and motor tasks as well (for reviews, see Dunlosky, Rawson, Marsh, Nathan, & Willingham, 2013;Rohrer, 2012).…”
Section: Abstract Interleaving Pronunciation Learning Discriminatmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported benefits of interleaving on the learning of geometric concepts (e.g., Taylor & Rohrer, 2010) and algebraic rules (e.g., Mayfield & Chase, 2002). A small but growing number of studies has also reported benefits of interleaving for other types of cognitive and motor tasks as well (for reviews, see Dunlosky, Rawson, Marsh, Nathan, & Willingham, 2013;Rohrer, 2012).…”
Section: Abstract Interleaving Pronunciation Learning Discriminatmentioning
confidence: 99%
“…Students worked through practice problems in an order that was either blocked by type of figure (i.e., all problems pertaining to one type of figure were finished before the student moved on to the next type of figure) or interleaved such that the same problems appeared in an order that was shuffled and unpredictable. On a later test requiring students to calculate the volumes for similar types of figures, students scored higher if they had learned the information through interleaving, as compared with blocking.Other studies have reported benefits of interleaving on the learning of geometric concepts (e.g., Taylor & Rohrer, 2010) and algebraic rules (e.g., Mayfield & Chase, 2002). A small but growing number of studies has also reported benefits of interleaving for other types of cognitive and motor tasks as well (for reviews, see Dunlosky, Rawson, Marsh, Nathan, & Willingham, 2013;Rohrer, 2012).…”
mentioning
confidence: 99%
“…Fonte: Elaboração dos autores relações, sem que houvesse necessidade de ensiná-las diretamente. Neste procedimento, um novo membro foi adicionado ao conjunto de estímulos para ser discriminado dos outros previamente dominados, o que é denominado de programação cumulativa (Mayfield & Chase, 2002). Mayfield e Chase (2002) argumentam que a justaposição de diferentes tipos de problemas, em uma programação cumulativa de ensino, possibilita a aprendizagem de múltiplas discriminações.…”
unclassified
“…1455 de número, a resolução de problemas de adição e subtração e o ensino de frações, para diferentes populações, inclusive, pessoas com desenvolvimento atípico (e.g., Escobal, Rossit, & Goyos, 2010;Lynch & Cuvo, 1995;Prado & de Rose, 1999;Santos, Cameschi, & Hanna, 2012;Santos, Simonassi, Rodrigues, & Magri, 2014). Diversas pesquisas visaram identifi car formas de tornar o aprendizado de Matemática mais fácil e efi caz pela avaliação de diferentes métodos de ensino ou do estabelecimento de comportamento pré-requisito (e.g., Levingston, Neef, & Cihon, & 2009;Mayfi eld & Chase, 2002) ou, ainda, por meio do desenvolvimento de estratégias especí-fi cas, como o emprego de uma balança virtual para resolver problemas de adição e de subtração (e.g., Iégas & Haydu, 2015). Também têm sido desenvolvidas propostas para o ensino de habilidades complexas como é o caso da Estatís-tica inferencial (e.g., Critchfi eld & Fienup, 2010;Fienup & Critchfi eld, 2011).…”
Section: Literatura Analítico-conductual Brasileña Sobre El Comportamunclassified